Response of diminazene-resistant and diminazene-susceptible Trypanosoma congolense to trreatment with diminazene when occuring as a mixed infection in goats. - Burudi, E.M.E. (University of Nairobi, 1992)
The research described in this thesis was carried out to investigate the phenotypic basis of resistance to diminazene (Berenil R) in Trypanosoma congolense. Earlier work has shown that, in both goats and mice, the majority of T. congolense trypanosomes which reappear following treatment with diminazene aceturate are sensitive to the dosage that was used. Such a phenomenon could be due to the ability of sensitive trypanosomes to survive treatment when mixed ,with resistant trypanosomes. Thus, the work described here was carried out to establish whether a diminazene-sensitive clone of T. congolense could survive treatment with diminazene aceturate at a dose of 7.0 mg/kg b.w. when mixed with a diminazene-resistant clone in goats. Since the study used two Savannahtype clones of T. congolense, the work necessitated the development of a polymerase chain reaction (peR) technique that could differentiate the two clones of T. congolense . .The 2 clones of T. congolense that were used were T. congolense IL 1180 . (a derivative of STIB 212 which is sensitive in goats to intramuscular [i/m] treatment with diminazene aceturate at a dose of 7.0 mg/kg b.w.) and T. congolense IL 3274 (a derivative of IL 2865, isolated from a cow in Burkina Faso, which is resistant in goats to i/m treatment with diminazene aceturate at a dose of 7.0 mg/kg b.w.). In order to distinguish the 2 clones, a peR technique was developed which utili sed a DNA sequence that is present in IL 1180, but not in IL 3274. A pair of 20 nt primers were developed on the basis of DNA sequence information for the ends of the cloned DNA sequence. The primers were then shown to amplify a 900 bp sequence from the plasmid in which the gene was cloned (P1616/5), and from genomic DNA of IL 1180. However, a similar product was not produced with IL 3274 genomic DNA. In further work, the 900 bp product amplified by PCR from p1616/5 was purified and labelled with 32p, in order to generate a probe specific for the trypanosome-specific PCR product. Using the above reagents, the first study endeavoured to establish the minimum amount of IL 1180 DNA that could be detected when mixed with 25 ng of IL 3274 DNA. When using ethidium bromide-staining of PCR products in an agarose gel, the minimum level of detection was 100 pg of IL 1180 DNA However, when such a gel was blotted and the filter hybridized with the [32p]_ labelled 900 bp product, the sensitivity was increased by 100-fold (i.e., to 1 pg). In an experiment to determine whether the diminazene-sensitive clone (IL 1180) could survive treatment with diminazene aceturate when mixed with a resistant clone (IL 3274), 24 goats were randomised into 3 groups of 5 goats each (Groups A, Band C) and 3 groups of 3 animals each (Groups D, E and F). Groups A and D were infected with IL 1180; Groups Band E were infected with IL 3274; and Groups C and F were infected with both clones simultaneously. All animals were infected intravenously, via the jugular vein, and animals that were treated were administered diminazene aceturate i/m at a dose of 7.0 mglkg b.w. Animals in Groups A and B were treated after all the goats in the respective groups had been detected parasitaemic. In contrast, goats in Group -C were not treated until all the animals in both Groups A and B had been detected parasitaemic, thereby ensuring that both trypanosome clones in these animals had fully developed by the time of treatment. Groups D, E and F served as nontreatment controls and also facilitated a comparison of the pathogenicity of the 2 clones individually and when mixed. Following treatment, all goats in all groups were monitored 3 times a week for 84 days for their levels of anaemia and parasitaemia. During the entire experiment, trypanosome stabilates were collected as follows from all animals; stabilates of goat blood, once a week; parasitaemic mouse blood as a result of inoculation with goat blood, once every 2 weeks; buffy-coat preparations of parasitaemic goat blood, twice a week. All 5 goats infected with IL 1180 and treated with diminazene aceturate (Group A) did not develop a relapse infection for the entire 84 days following treatment. This was in contrast to goats infected with IL 3274 (Group B) and those infected with both clones (Group C) in which 5 out of 5 and 4 out of 5 relapses occurred, respectively. All the non-treatment control goats infected with IL 3274 developed a severe anaemia (packed Cell Volume (PCV]< 12%). along with a high level of parasitaemia, and were therefore removed from the experiment since this level of anaemia was deemed fatal. In contrast, all nontreatment goats infected with IL 1180 maintained their PCV between 15% and 20% throughout the entire experiment. Finally, of the 3 non-treatment control goats infected with both clones, one developed a severe anaemia and was removed from the experiment; the remaining 2 maintained their PCV above 12% during the entire experimental period. Thus, on the basis of ability to maintain PCV, it can be concluded that the drug-resistant clone was more pathogenic than the drug-sensitive clone. In order to determine that IL 1180 was present in goats with mixed infections at the time of treatment (Group C), goat blood stabilates collected 3 days before treatment were expanded in irradiated mice. Goat buffy-coat preparations taken on the day of treatment, were also examined. However, while trypanosomes in goat blood were expanded in mice, trypanosomes in buffy-coats were examined directly. Goat blood stabilates of relapse trypanosome populations occurring in the same animals on days 18, 32, 46 and 60 following treatment were also examined; each stabilate was expanded in irradiated mice. The DNA from all the aforementioned samples were screened for the presence of IL 1180 using the PCR-technique described above, and the [32P]-labelled 900 bp probe. For each reaction, 25 ng of genomic DNA was used as the template. The results demonstrated that IL 1180 was present in all mixed infections prior to treatment, but was absent in all relapse populations following treatment at the level of detection of the radiolabelled probe (i.e., 1 pg/25 ng total DNA). The data therefore indicated that a diminazene-sensitive trypanosome population is unable to survive treatment with diminazene when mixed with a diminazeneresistant population.